Bio-based polyurethane foams from acacia mangium polyol: Analyzing the impact of polyol residue, surfactant, and water on foam properties - Ismawati Palle; Naruhito Hori; Akio Takemura (Institut Kimia Malaysia, 2025)
This study investigated the synthesis of polyurethane foam using acacia mangium (AM) polyol and its residue, with varying percentages of surfactant and water as blowing agents. The foam formulation included polymeric methylene bis(phenyl isocyanate) (PMDI), a catalyst mixture of triethylene diamine (TEDA-L33) and pentamethyldiethylene triamine (TOYOCAT-ET), polysiloxane (SH193) as the surfactant, and water as the blowing agent. The effect of incorporating AM polyol residue was first examined, followed by an analysis of the impact of the surfactant and blowing agent on the foam’s properties, including kinetic rate, morphology, apparent density, water absorption, and compression behaviour. FTIR and DMA analyses were performed to assess the structural and mechanical properties of the foam. Results indicated that the addition of AM polyol residue significantly increased the foam density. However, reduced interfacial bonding between the residue and foam structure led to lower compression strength and higher water absorption. The study further showed that variations in water and surfactant content significantly influenced foam properties: increasing the water and surfactant content reduced foam density, accelerated the reaction between water and isocyanate (shortening the cream time), and enhanced nucleation and cell size. These findings suggest that am polyurethane foam has potential as a sustainable alternative in industries seeking eco-friendly materials.